2019
DOI: 10.2196/14239
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Healthy Eating and Fitness Mobile Apps in the Formation of Maladaptive Eating and Exercise Behaviors in Young People

Abstract: BackgroundHealthy eating and fitness mobile apps are designed to promote healthier living. However, for young people, body dissatisfaction is commonplace, and these types of apps can become a source of maladaptive eating and exercise behaviors. Furthermore, such apps are designed to promote continuous engagement, potentially fostering compulsive behaviors.ObjectiveThe aim of this study was to identify potential risks around healthy eating and fitness app use and negative experience and behavior formation among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 69 publications
0
60
2
Order By: Relevance
“…They liked apps that were free, easy to use, provided visual and auditory cues, and had game-like rewards, but they did not want to link the apps to social media [ 48 ]. Findings from an English study that involved a survey, workshops, and interviews with young people aged 18 to 25 years showed that a calorie-counting app was the most popular and was used by almost half of the participants [ 49 ]. Many participants had discontinued using a health or fitness app, however, citing lack of interest, time, or motivation as reasons.…”
Section: Resultsmentioning
confidence: 99%
“…They liked apps that were free, easy to use, provided visual and auditory cues, and had game-like rewards, but they did not want to link the apps to social media [ 48 ]. Findings from an English study that involved a survey, workshops, and interviews with young people aged 18 to 25 years showed that a calorie-counting app was the most popular and was used by almost half of the participants [ 49 ]. Many participants had discontinued using a health or fitness app, however, citing lack of interest, time, or motivation as reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Some articles focus on the problems related to fitness apps and the adherence to hegemonic beauty canons. In this line of research, Honary et al (2019) concluded that the use of these apps might increase social pressure to achieve unrealistic beauty ideals and could thus increase the incidence of eating problems, such as anorexia or excessive physical exercise. Another issue of concern relates to the privacy of and the large amount of personal data collected by these apps ( Adhikari et al, 2014 ).…”
Section: Main Topics Analyzed and Lines Of Researchmentioning
confidence: 99%
“…According to Honary et al (2019), "results show that, ironically, people are more likely to make dietary decisions when there is a nutritious object than when there is not." Nutritious choices are increasingly favored, and 72 percent of customers choose to be healthier while dining outside their homes, such as in grocery stores like restaurants (Cohen & Babey, 2012).…”
Section: Food Attributesmentioning
confidence: 99%